1976
DOI: 10.1161/01.cir.53.5.828
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dobutamine on regional myocardial blood flow and ventricular performance during acute and chronic myocardial ischemia in dogs.

Abstract: The data from this study document that dobutamine is a powerful inotropic agent in anesthetized dogs with acute myocardial ischemia and in awake, unsedated ones with chronic myocardial infarction. Dobutamine significantly increases heart rate at relatively small doses in anesthetized dogs with acute myocardial ischemia but considerably larger amounts of dobutamine are required to significantly increase heart rate in awake, unsedated dogs with myocardial infarction. Dobutamine also significantly increases regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(28 citation statements)
references
References 11 publications
3
24
0
1
Order By: Relevance
“…With prenalterol, 20 jig kg-', both RMBF and regional contractility were decreased, a picture similar to that observed with atrial pacing at 175 beats min-'. These results must be considered in the light of those previously reported in anaesthetized (Marshall & Parratt, 1976;Willerson et al, 1976;Warltier et al, 1981;Rude etal., 1982Rude etal., , 1983 or in conscious dogs (Vatner & Baig, 1979;Liang et al, 1981) treated with dobutamine or dopamine during coronary artery occlusion or stenosis. Despite some differences, all these studies concluded that P-adrenoceptor agonists that induce coronary vasodilatation do not always cause a 'coronary steal phenomenon' nor necessarily enhance myocardial injury providing that coronary perfusion pressure is maintained and above all that tachycardia remains limited.…”
Section: Discussionsupporting
confidence: 60%
“…With prenalterol, 20 jig kg-', both RMBF and regional contractility were decreased, a picture similar to that observed with atrial pacing at 175 beats min-'. These results must be considered in the light of those previously reported in anaesthetized (Marshall & Parratt, 1976;Willerson et al, 1976;Warltier et al, 1981;Rude etal., 1982Rude etal., , 1983 or in conscious dogs (Vatner & Baig, 1979;Liang et al, 1981) treated with dobutamine or dopamine during coronary artery occlusion or stenosis. Despite some differences, all these studies concluded that P-adrenoceptor agonists that induce coronary vasodilatation do not always cause a 'coronary steal phenomenon' nor necessarily enhance myocardial injury providing that coronary perfusion pressure is maintained and above all that tachycardia remains limited.…”
Section: Discussionsupporting
confidence: 60%
“…Thus, dobutamine use may potentially be detrimental in patients with limited coronary artery reserve in whom oxygen delivery cannot rise adequately to meet additional myocardial oxygen demand. 3 Amrinone, a nonglycosidic, nonadrenergic, cardiotonic agent, selectively inhibits type III phosphodiesterase. 4 When administered intravenously to patients with congestive heart failure, amrinone produces increases in cardiac performance similar in magnitude to the effect seen with dobutamine.7-10 In addition to its positive inotropic action, amrinone causes substantial arterial and venous vasodilation, and thus reduces both cardiac afterload and preload.…”
mentioning
confidence: 99%
“…These factors include isoprenaline, ouabain and tachycardia (Maroko, Kjekshus, Sobel, Watanase, Covell, Ross & Braunwald, 1971) and (Redwood, Smith & Epstein, 1972). Dobutamine has been shown in both the anaesthetized and conscious dog, with myocardial ischaemia, to increase myocardial contractility as much if not more than myocardial blood flow and if heart rate were to increase in addition, then the extent of myocardial damage would be greater (Willerson et al, 1976). Thus, despite the lack of effect on heart rate, U.K. 14275 should be used with caution in patients with acute myocardial infarction unless there is evidence of left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%